Economic Determinants of Fund Financial Arrangements - Santaella, Julio (IMF Working Papers; Working Paper, 1994)
This paper analyses empirically the economic factors that lead to approval of Fund financial arrangements. We account for both the economic variables that induce a country to seek an arrangement with the Fund ("demand-side" factors) and the macroeconomic policy commitments that the Fund considers when deciding whether to approve it ("supply-side" factors). Using a pooled sample of annual observations for 91 developing countries over 1973-1991, we obtain maximum likelihood estimates of bivariate and univariate probit equations to determine the probability of approval of a financial arrangement for a given country in a given year. A number of our chosen demand-side and supply-side variables are statistically significant determinants of the approval of a Fund arrangement, and the overall explanatory power of the equations is high.